KAJIAN POLA PERGERAKAN WISATAWAN DI OBJEK WISATA ALAM KABUPATEN MALANG - Myrna Sukmaratri (Universitas Merdeka Malang, 2018)
Malang Regency has diverse tourism objects and spread throughout the districts. Those attractions include natural tourism such as beaches, mountains, and lakes; man-made tourism such as tourist park; and cultural tourism such as art artifacts/historical buildings and dance/craft attractions. Therefore, Malang Regency become one of tourism destination of regional and even international scale. However, the problem is tourist’s arrival only concentrated in some natural tourism. The inequality of tourist’s visit in natural tourism of Malang Regency can be caused by several factors such as accessibility, the condition of tourism infrastructure, as well as promotion and information that has not been separated widely. This study aims to examine the pattern of tourist movements in natural tourism of Malang Regency and then will be explored based on the tourists motivation and the characteristics of tourism destinations. Market basket analysis is used to know the dominant of tourist route. The tourists movement in natural tourism of Malang Regency form route trip of single point, base site, stopover, and chaining loop. Furthermore, the maximum tourist movement is four destinations during their tour. This tourist movement is based on tourists motivation and the conditions of the visited tourism such as adjacent tourist locations, length of travel, road conditions, and availability of public transport. Based on the analysis results, the most frequently visited route is Coban Rondo- Batu City. It is based on the proximity of the distance and the types of attractions offered by each tourism objects